THE INFLUENCE OF ACADEMIC SUPERVISION BY THE PRINCIPAL AND TRAINING ON THE PEDAGOGICAL COMPETENCE OF TEACHERS AT MADRASAH TSANAWIYAH NURUL HUDA SOUTH JAKARTA - Firdayanti, Nabilah (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of academic supervision and training on pedagogical competence of teachers at Madrasah Tsanawiyah Nurul Huda. The research method used in this study uses a quantitative approach. The population is 41 people. The sampling technique uses saturated samples so that the number of samples in this study is 44 respondents. The data analysis technique uses simple linear regression. The results of the study show that there is a positive and significant effect of the effect of organizational culture on the employee performance at Bungong Jaroe Playground and Restaurant. This is evidenced by the F-count value > F-table, which is 27.951 > 3.24. The probability value (significance) = 0.000 is below 0.050.